السياحة المظلمة , مفهومها , امكانات تنميتها و أهميتها - خطاب, نياز عبدالعزيز (Sulaimani Journal for Humanities, 2018)
Dark tourism is a new tourist pattern, in which people visit areas and places that have witnessed horrific historical events, whether human or natural, claiming people's lives or causing certain human suffering, such as wars, internal conflicts and disasters. This type of tourism is considered the dark side of human nature. Dark tourism has been defined as being manifested in travel to sites linked to death and human tragedies. Dark tourism sites are characterized by their diversity and varying degrees of severity. The reasons for tourists' visit to the dark tourist sites are also varied, the most prominent of which are: vision to believe in, learning and taking lessons, the attractions of the famous death incidents, ruthlessness in communicating with heritage, suspense and search for risks.